2023
DOI: 10.3390/ani13020249
|View full text |Cite
|
Sign up to set email alerts
|

Stress Evaluation of Mouse Husbandry Environments for Improving Laboratory Animal Welfare

Abstract: Animal welfare is recognized as essential for the coexistence of humans and animals. Considering the increased demand and interest in animal welfare, many methods for improving animal welfare are being devised, but which method reduces animal stress has not been scientifically verified. Therefore, reducing animal stress by providing a proper breeding environment and environmental enrichment can be the basis for animal study. In this study, stress levels were assessed based on the mouse-breeding environment. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Mice that were changed from sharing a cage with littermates to living alone showed higher fecal corticosterone metabolites than those maintained in the group after the first week, although levels normalized after 1 month. These same results were recently observed in adult CD1 mice housed in the same conditions as our animals, in a ventilated rack with environmental enrichment [ 50 ], which may indicate habituation to the new situation. Due to the nature of our experimental design, we were unable to determine when exactly corticosterone metabolite levels normalized, and this is one of our study’s limitations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Mice that were changed from sharing a cage with littermates to living alone showed higher fecal corticosterone metabolites than those maintained in the group after the first week, although levels normalized after 1 month. These same results were recently observed in adult CD1 mice housed in the same conditions as our animals, in a ventilated rack with environmental enrichment [ 50 ], which may indicate habituation to the new situation. Due to the nature of our experimental design, we were unable to determine when exactly corticosterone metabolite levels normalized, and this is one of our study’s limitations.…”
Section: Discussionsupporting
confidence: 90%
“…As previously reported for CD1 male mice [ 48 , 49 , 50 ], social isolation for 4 weeks did not affect body weight gain. Similarly, our results revealed that social isolation did not modify RBC parameters.…”
Section: Discussionsupporting
confidence: 83%
“…A similar scheme was applied for the first and second booster doses for the experimental and control groups. After immunization, animals were regularly monitored to observe their response ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, palatable gel diet energy and transport food (SAFE ®, , Rosenberg, Germany) in a Petri dish was placed in the cage bedding. This approach allowed the animals to adapt to their new housing conditions for a 7-day acclimation period prior to surgery, minimizing possible stress and anxiety associated with novel food and environments [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%